SARS-CoV-2: characteristics and current advances in research - Yang, Yicheng; Xiao, Zhiqiang; Ye, Kaiyan; He, Xiaoen; Sun, Bo; Qin, Zhiran; Yu, Jianghai; Yao, Jinxiu; Wu, Qinghua; Bao, Zhang; Zhao, Wei (Virology journal, 2020)
Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 infection has spread rapidly across the world and become an international public health emergency. Both SARS-CoV-2 and SARS-CoV belong to subfamily Coronavirinae in the family Coronaviridae of the order Nidovirales and they are classified as the SARS-like species while belong to different cluster. Besides, viral structure, epidemiology characteristics and pathological characteristics are also different. We present a comprehensive survey of the latest coronavirus—SARS-CoV-2—from investigating its origin and evolution alongside SARS-CoV. Meanwhile, pathogenesis, cardiovascular disease in COVID-19 patients, myocardial injury and venous thromboembolism induced by SARS-CoV-2 as well as the treatment methods are summarized in this review.